2019
DOI: 10.1063/1.5120385
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast acoustic phonon scattering in CH3NH3PbI3 revealed by femtosecond four-wave mixing

Abstract: Carrier scattering processes are studied in CH3NH3PbI3 using temperature-dependent four-wave mixing experiments. Our results indicate that scattering by ionized impurities limits the interband dephasing time (T2) below 30 K, with strong electron-phonon scattering dominating at higher temperatures (with a timescale of 125 fs at 100 K). Our theoretical simulations provide quantitative agreement with the measured carrier scattering rate and show that the rate of acoustic phonon scattering is enhanced by strong sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Many previous works on carrier dephasing 10,11 and thermalization 5 in three dimensional lead halide perovskites have clearly identified the role of anharmonic lattice interactions in electronic processes. On a very similar note, albeit in the context of electrically neutral excitons, we find that all the phonons that dress the excitons and thus are the integral components of the exciton polaron wavefunction exhibit strong anharmonicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous works on carrier dephasing 10,11 and thermalization 5 in three dimensional lead halide perovskites have clearly identified the role of anharmonic lattice interactions in electronic processes. On a very similar note, albeit in the context of electrically neutral excitons, we find that all the phonons that dress the excitons and thus are the integral components of the exciton polaron wavefunction exhibit strong anharmonicity.…”
Section: Discussionmentioning
confidence: 99%
“…2 The optical phonons, in particular, have been identified to play a critical role in the electronic dynamics via strong polaronic coupling mechanisms. 3 The consequences of the strong phonon interactions in the structural stabilization, 4 carrier thermalization, 5 carrier recombination, 6,7 carrier transport 8,9 and dephasing dynamics 10,11 are widely reported. The acoustic modes, on the other hand, determine the thermal properties of the material, including thermal conductivity, molar specific heat, and thermal expansion of the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first direct experimental observation of a photon echo in lead halide perovskite bulk crystals. In previous FWM studies of lead halide perovskite thin films, 35,38 the PE presence was only assumed.…”
Section: Resultsmentioning
confidence: 99%
“…34 Information on structure of energy transitions and coherent optical properties of hybrid lead-halide perovskites is barely known for bulk crystals and mostly based on studies of nanoplatelets 35 and thin films. [36][37][38][39][40] Exciton fine structure splitting of ∼ 200 µeV has been measured in MAPbBr3 bulk crystal. 41 It was shown that organic-inorganic perovskites have interesting features associated with the organic cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation